2012
DOI: 10.1021/jm300710j
|View full text |Cite
|
Sign up to set email alerts
|

Radiofluorinated Derivatives of 2-(Phosphonomethyl)pentanedioic Acid as Inhibitors of Prostate Specific Membrane Antigen (PSMA) for the Imaging of Prostate Cancer

Abstract: For prostate cancer, prostate specific membrane antigen (PSMA) has been identified as a diagnostic and therapeutic target. Fluorinated derivatives of 2-(phosphonomethyl)pentanedioic acid were designed and synthesized to explore whether this fluorine-substituent is tolerated in the pentanedioic acid moiety that is common to almost all PSMA targeting small molecule inhibitors. The binding affinities of the racemic and individual stereoisomers of 2-fluoro-4-(phosphonomethyl)pentanedioic acid were determined and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Depending on the properties of drug molecules one or more pathways are likely to dominate. Thus in order to elucidate the mechanism of 2-PMPA delivery via intranasal route to the CSF and brain, and to get quantitative the measurements in primate brain radiolabeled agents such as radiofluorinated 2-PMPA [ 73 ] may provide a more viable option. Future studies to evaluate such mechanisms are underway.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the properties of drug molecules one or more pathways are likely to dominate. Thus in order to elucidate the mechanism of 2-PMPA delivery via intranasal route to the CSF and brain, and to get quantitative the measurements in primate brain radiolabeled agents such as radiofluorinated 2-PMPA [ 73 ] may provide a more viable option. Future studies to evaluate such mechanisms are underway.…”
Section: Discussionmentioning
confidence: 99%
“…A series of preclinical studies evaluated the role of radiolabeled small-molecule PSMA inhibiting ligands for imaging of human PCa using various radionuclides such as 11 C 32 , 18 F 33 , 123 I 34 , 99m Tc 34 - 36 , and 68 Ga 37 , 38 . The compounds used in these studies can be classified into three groups: (1) the urea-based compounds, (2) the glutamate phosphoramidates and (3) the 2-(phosphinylmethyl) pentanedioic acids 21 ( figure 1 ). Overall, the PSMA ligands tested in these preclinical studies showed high tumor uptake peaking at 0.5 - 1 h in mice with PSMA-expressing tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the expression of PSMA in the prostate is nearly 100-fold higher than in other tissues and prostate cancer exhibits a tenfold higher expression than the healthy prostate, PSMA has become a conspicuous target for nuclear medicine diagnostics and therapy very recently. Since the 1990s several radiopharmaceuticals directed against PSMA were established [ 8 12 ]. Today several groups use PSMA-based PET for the diagnostics of PCa with excellent sensitivity based on a very high contrast [ 13 17 ].…”
Section: Introductionmentioning
confidence: 99%